Leadership as Identity: the Focus in African Literature - Paasche, Karin Ilona Ilona (Respectus Philologicus, 2017)
The Panama Papers leakage implicated several African leaders in global corruption deals. It confirmed perceptions that these leaders care little for their people. African leaders who overstay term limits are the focus of Western democratic ire. Pro-democracy movements, the overthrow of regimes characterised as undemocratic gain unquestioned media coverage and praise. African leaders are summoned to the International Criminal Court in The Hague; their societies debate whether justice can be administered from outside. Increasingly, voices question African political and developmental processes. African Literature participates in struggles defining modern Africa’s search for identity and its own definition of leadership. It points to possibilities rooted in African Oral Tradition and in customs predating various colonial systems. Leadership forms that societies choose are closely linked to perceptions of identity. This paper examines the crisis of identity which has resulted in Africa’s crisis of leadership and looks at approaches taken by African writers and filmmakers: Malian filmmaker Cheik Oumar Sissoko’s film La Genèse (1999), South African writer Zakes Mda’s novels Ways of Dying(1995), Heart of Redness (2000).